CCAAT/Enhancer Binding Protein α Is a Regulatory Switch Sufficient for Induction of Granulocytic Development from Bipotential Myeloid Progenitors - Radomska, Hanna S. (American Society for Microbiology, 1998)
The transcription factor CCAAT/enhancer binding protein α (C/EBPα) regulates a number of myeloid cell-specific genes. To delineate the role of C/EBPα in human granulopoiesis, we studied its expression and function in human primary cells and bipotential (granulocytic/monocytic) myeloid cell lines. We show that the expression of C/EBPα initiates with the commitment of multipotential precursors to the myeloid lineage, is specifically upregulated during granulocytic differentiation, and is rapidly downregulated during the alternative monocytic pathway. Conditional expression of C/EBPα alone in stably transfected bipotential cells triggers neutrophilic differentiation, concomitant with upregulation of the granulocyte-specific granulocyte colony-stimulating factor receptor and secondary granule protein genes. Moreover, induced expression of C/EBPα in bipotential precursors blocks their monocytic differentiation program. These results indicate that C/EBPα serves as a myeloid differentiation switch acting on bipotential precursors and directing them to mature to granulocytes.